DETERMINING A FREQUENCY FOR TTFIELDS TREATMENT BASED ON AN ELECTRICAL CHARACTERISTIC OF TARGETED CANCER CELLS - BOMZON, ZEEV; ZEEVI, EINAV; WENGER, CORNELIA; GILADI, MOSHE (2020)
Cancer treatment using TTFields (Tumor Treating Fields) can be customized to each individual subject by obtaining cancer cells from the subject, determining an electrical characteristic (e.g., dielectrophoretic forces, cell membrane capacitance, etc.) of the cancer cells, determining a frequency for the TTFields based on the determined electrical characteristic, and treating the cancer by applying TTFields to the subject at the determined frequency. In addition, cancer treatment can be planned for each individual subject by obtaining cancer cells from the subject, determining an electrical characteristic of the cancer cells, predicting whether TTFields would be effective to treat the cancer based on the determined electrical characteristic, and treating the subject by applying TTFields if the prediction indicates that TTFields would be effective. Le traitement du cancer à l'aide de champs TT (champs de traitement de tumeur) peut être personnalisé pour chaque sujet individuel en obtenant des cellules cancéreuses à partir du sujet, en déterminant une caractéristique électrique (par exemple, des forces diélectrophorétiques, une capacité de membrane cellulaire, etc.) des cellules cancéreuses, en déterminant une fréquence pour les champs TT sur la base de la caractéristique électrique déterminée, et en traitant le cancer en appliquant des champs TT au sujet à la fréquence déterminée. De plus, le traitement du cancer peut être planifié pour chaque sujet individuel en obtenant des cellules cancéreuses à partir du sujet, en déterminant une caractéristique électrique des cellules cancéreuses, en prédisant si des champs TT seraient efficaces pour traiter le cancer sur la base de la caractéristique électrique déterminée, et en traitant le sujet en appliquant des champs TT si la prédiction indique que des champs TT seraient efficaces.